Conceptualizing Precarious Employment: Mapping Wage Work Across Social Location and Occupational Context - Vosko, Leah F.; Cranford, Cynthia J. (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
[A]dvances a new methodological approach to understanding precarious wage work.... This approach considers how race and gender, as they intersect with occupation, shape and, in turn, are shaped by precarious employment. Its main empirical finding is that a "racialized gendering of jobs" characterizes the contemporary Canadian labour market. –From editor's introductory chapter (p. 34).
https://www.mqup.ca/precarious-employment-products-9780773529618.php
Keywords: Industrial hygiene; Labor Unions; Labor laws and legislation; Labor market; Temporary employment